Autonomic Dysfunction Manifesting With Asymmetric Face Flushing and Paroxysmal Nonconvulsive Episodes. (December 2013) - Pavone, Piero; Praticò, Andrea Domenico; Micali, Giuseppe; Greco, Filippo; Ruggieri, Martino; Pavone, Lorenzo
Asymmetric face flushing, known as harlequin syndrome, is an autonomic disorder that occurs with other dysfunctions or in isolation. It may be secondary to organic causes or unknown in origin. The latter, which is uncommon in childhood, is considered benign. We report on a boy who first showed this anomaly at 4 years of age, followed up for 6 years. During this time, we saw an increase in the frequency and duration of the episodes of asymmetric face flushing. In the past months, the episodes were associated with a wider involvement of autonomic symptoms, consisting of severe localized headache, lack of coordination, asymmetric sweating, and a loss of strength that lasted about 30 minutes. A review list of young patients affected by this condition is reported.